Is There a Relationship Between Cyber-Dependent Crime, Autistic-Like Traits and Autism? - Payne, Katy-Louise; Russell, Ailsa; Mills, Richard; Maras, Katie; Rai, Dheeraj; Brosnan, Mark (Journal of Autism & Developmental Disorders, 2019)
International law enforcement agencies have reported an apparent preponderance of autistic individuals amongst perpetrators of cyber-dependent crimes, such as hacking or spreading malware (Ledingham and Mills in Adv Autism 1:1–10, 2015). However, no empirical evidence exists to support such a relationship. This is the first study to empirically explore potential relationships between cyber-dependent crime and autism, autistic-like traits, explicit social cognition and perceived interpersonal support. Participants were 290 internet users, 23 of whom self-reported being autistic, who completed an anonymous online survey. Increased risk of committing cyber-dependent crime was associated with higher autistic-like traits. A diagnosis of autism was associated with a decreased risk of committing cyber-dependent crime. Around 40% of the association between autistic-like traits and cyber-dependent crime was mediated by advanced digital skills.